Computational anharmonic force fields of CuSH and CuSD. (6th July 2017) - Zhao, Yanliang; Wang, Meishan; Yang, Chuanlu; Ma, Xiaoguang; Yu, Yongjiang
Abstract: The anharmonic force fields and spectroscopy constants for the ground electronic state ( X ˜ A 1 ′ ) of copper hydrosulfide (CuSH) have been investigated using various theoretical methods (MP2, B3LYP, B3P86, B3PW91) and basis sets (cc-pVDZ, cc-pVTZ). It turns out that the MP2/cc-pVTZ theoretical level is reasonable to study the molecular spectroscopic properties of CuSH. The calculated molecular structure, rotational constants, vibrational frequencies, centrifugal distortion constants, vibration–rotation interaction constants, force constants and Coriolis coupling constants of CuSH can be utilized to provide theoretical predictions of the spectroscopic properties and can be conducive to chemical applications such as the hydrodesulfurisation of fossil feed-stocks. Besides, the calculated force constants, evaluated in mass-weighted normal coordinates using a finite-difference approach, can be used to analyze the potential energy surface of CuSH. In addition, the anharmonic force fields of CuSD have been also investigated using the MP2 method.